1994
DOI: 10.1017/s0043174500076621
|View full text |Cite
|
Sign up to set email alerts
|

Germination, Emergence, and Seedling Establishment of Buffalo Gourd (Cucurbita foetidissima)

Abstract: Studies were conducted to determine the effects of scarification, temperature, osmotic potential, and pH on seed germination of buffalo gourd and to examine seedling emergence and establishment. Mechanical and chemical scarification did not increase germination compared to non-scarified seed. Seed germinated at constant temperatures in the dark from 15 to 37 C with optimum germination at 25 C. As osmotic potentials became more negative from −0.1 to −0.8 MPa, germination decreased from 77 to 53%. Germination in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Germination of burcucumber (Sicyos angulatus L.) seeds occurred over a wide range of temperatures but was reduced at temperatures below 20 C and above 30 C (Mann et al 1981). Similarly, buffalo gourd (Cucurbita foetidissima Kunth) germination occurred in the dark at constant temperatures ranging from 15 to 37 C, with optimum germination at 25 C (Horak and Sweat 1994).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Germination of burcucumber (Sicyos angulatus L.) seeds occurred over a wide range of temperatures but was reduced at temperatures below 20 C and above 30 C (Mann et al 1981). Similarly, buffalo gourd (Cucurbita foetidissima Kunth) germination occurred in the dark at constant temperatures ranging from 15 to 37 C, with optimum germination at 25 C (Horak and Sweat 1994).…”
Section: Resultsmentioning
confidence: 99%
“…Other weed species from the Cucurbitaceae family exhibit the same emergence characteristics. Horak and Sweat (1994) reported that surface-sown seeds of buffalo gourd did not germinate, but emergence was greatest (. 50%) at 2-to 8-cm sowing depth.…”
Section: Resultsmentioning
confidence: 99%
“…This stands in contrast to invasive vine species like Brunnichia ovata (Shaw et al . 1991) and Cucurbita foetidissima (Horak & Sweat 1994), who require at least some soil coverage for germination.…”
Section: Resultsmentioning
confidence: 99%
“…Again, this trait of much higher emergence rates from seeds near the soil surface is shared with a wide range of invasive weeds, including Eupatorium adenophorum (Lu et al 2006), Nicandra physalodes (Watanabe et al 2002), and Cortaderia jubata (Drewitz & DiTomaso 2004). This stands in contrast to invasive vine species like Brunnichia ovata (Shaw et al 1991) and Cucurbita foetidissima (Horak & Sweat 1994), who require at least some soil coverage for germination.…”
Section: Effect Of Sowing Depthmentioning
confidence: 99%
“…The amount of energy reserves required to support elongation of the seedling from deeper depths and a reduction in light with increased planting depth have been suggested as reasons for reduced weed seedling emergence from greater depths (Benech-Arnold et al 2013). Tillage operations can influence weed seed placement within the soil profile (Horak and Sweat 1994). These data suggest that tillage deeper than 5 cm can bury smellmelon seed in the soil and reduce seedling emergence.…”
Section: Resultsmentioning
confidence: 99%